The Eurasian economic union and legal regulation of integration processes in the post-Soviet space - Nakysheva, M.K. (Journal of actual problems of jurisprudence, 2018)
Нe emergence and establishment of the Eurasian Economic Union, as well as the interaction of the integration process, which made possible the emergence of the Customs Union. And also, on the effective functioning of the Eurasian Economic Union and that it is impossible to imagine without a co-ordinated macroeconomic policy, which provides for the development and implementation of joint actions of Member States of the Union in order to achieve a balanced economic development Key words: Eurasian Union, the Eurasian Economic Union, the Customs Union, the Eurasian Economic Alliance.